2003
DOI: 10.1021/ma0257447
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of A2 with B3 Monomers:  A Facile Approach to Hyperbranched Poly(aryl ester)s

Abstract: Hyperbranched polymers have received significant attention due to their unique combination of low viscosity, excellent solubility, and facile synthesis. This paper describes an efficient approach to hyperbranched poly(aryl ester)s via the polycondensation of A2 and B3 monomers. A dilute bisphenol A (A2) solution was added slowly to a dilute 1,3,5-benzenetricarbonyl trichloride (B3) solution at 25 °C to prepare hyperbranched poly(aryl ester)s in the absence of gelation. The molar ratio of A2:B3 was maintained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 43 publications
4
113
2
Order By: Relevance
“…The integral values of dendritic, linear and terminal unit proton resonances of benzene tricarboxylic acid (around d 8.74-8.68 ppm) were used for the estimation. 9,10,25,26 The DB value is found to be 0.52, which agree well with general scale for the hyperbranched polymers made by one-pot procedure. 53 …”
Section: Synthesis Of Photoactive Epoxy Terminated Linear and Hyperbrsupporting
confidence: 81%
See 1 more Smart Citation
“…The integral values of dendritic, linear and terminal unit proton resonances of benzene tricarboxylic acid (around d 8.74-8.68 ppm) were used for the estimation. 9,10,25,26 The DB value is found to be 0.52, which agree well with general scale for the hyperbranched polymers made by one-pot procedure. 53 …”
Section: Synthesis Of Photoactive Epoxy Terminated Linear and Hyperbrsupporting
confidence: 81%
“…7 Limited availability of AB n monomers increases the use of readily available A 2 þ B 3 monomers for the synthesis of HBP. 8,[9][10][11] After preliminary work by Kim 12 on hyperbranched liquid crystalline polymers, (HBLCPs), synthesized by the AB n approach, the revolutionary work in this field was carried out by Percec et al, [13][14][15][16][17][18] Shibaev et al, 19 and others [20][21][22][23] have reported on photo-addressable dendritic polymers (PADLCPs) containing both mesogenic and photochromic groups. PADLCPs have shown enhanced physicochemical properties and photo and thermally induced physical changes as compared with linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…glycerol, in the presence of lipase and chemical catalysts to form hyperbranched polymers [1][2][3][4][5][6][7]. Understanding the relationship between D.B% and the physical and chemical properties of hyperbranched polymers is necessary to identify potential applications.…”
Section: Open Accessmentioning
confidence: 99%
“…[1][2] The former approach has mainly been achieved by the polycondensation of multifunctional monomers such as AB 2 , AB 2 + B y 24 and A 2 + B y type structures. 25 Meanwhile, the latter method has been based on a specific method called Ring-opening Multibranching Polymerisation (ROMBP) of latent AB 2 monomer, i.e. the ring-opening polymerisation of cyclic monomers in which the initiator is attached to the monomer ring.…”
Section: Introductionmentioning
confidence: 99%